Comparative short-term efficacy of Janus kinase 1 inhibitors and anti-interleukin-13 antibodies in atopic dermatitis: a retrospective cohort analysis based on real-world data - Sato, Emi; Obonai, Naoko; Iwata, Mayuko; Ito, Kotaro; Imafuku, Shinichi (Frontiers in Immunology, 2025)
IntroductionMolecular targeted therapies, including advanced atopic dermatitis (AD) treatment with Janus kinase 1 inhibitors (JAK1i) and anti-interleukin-13 antibodies (IL-13Ab), are emerging as effective options. However, the predictive biomarkers for treatment responses remain unclear. Therefore, this study compared the short-term efficacy of JAK1i and IL-13Ab and explored relevant biomarkers.MethodsThis retrospective analysis was conducted in 75 patients with moderate-to-severe AD treated at Fukuoka University Hospital. Relevant biomarkers, including eosinophil count and thymus and activation-regulated chemokine (TARC) levels, were measured at baseline and 3 months. Eczema Area and Severity Index (EASI) and Peak Pruritus Numerical Rating Scale (PP-NRS) scores were also assessed.ResultsPatients received JAK1i (n=37; abrocitinib, n=16; upadacitinib, n=21) or IL-13Ab (n=38; lebrikizumab, n=21; tralokinumab, n=17). At 3 months, no significant difference was observed between JAK1i and IL-13Ab in achieving EASI 75 (odds ratio [OR] = 0.83, p=0.76) or in the incidence of adverse events (OR = 1.40, p=0.55). However, JAK1i was associated with higher odds of achieving PP-NRS 4 (OR=9.36, p=0.0063) and PP-NRS 0/1 (OR=34.61, p<0.0001). In the JAK1i group, eosinophil count reduction correlated with EASI improvement (univariate: R=0.525, p=0.0009; adjusted: β = 0.567, p=0.0004). In the IL-13Ab group, TARC reduction correlated with EASI improvement (univariate: R=0.677, p<0.0001; adjusted: β = 0.661, p<0.0001).ConclusionJAK1i showed greater antipruritic effects than IL-13Ab at 3 months, likely due to interleukin (IL)-31 inhibition. Eosinophil count reduction was the most reflective biomarker of JAK1i efficacy, potentially due to IL-5 suppression, whereas TARC improvement was significantly associated with patients’ treatment response to IL-13Ab. These findings highlight the need for further long-term studies.